On Historicizing Epistemology : an Essay. - Rheinberger, Hans-Jrg (Cultural memory in the present., 2010)
This book shows how, from the late nineteenth to the late twentieth century, the philosophy of science was increasingly confronted with historical questions and how it became historicized accordingly.